Evaluating Enviromental Mitigatio and Sustainability Practices in the Construction of the Trans-Sumatera Toll Road - Andriansyah, Arief; Abduh, Ridwan M; Paramita, Galuh (WISE Pendidikan Indonesia, 2024)
The construction of the Trans-Sumatera Toll Road, part of Indonesia’s National Strategic Projects (PSN), offers significant economic benefits but also poses environmental challenges, particularly air pollution from construction activities. This study evaluates air quality deterioration due to heavy machinery use, material transportation, and excavation. A quantitative approach was employed through field surveys, environmental monitoring, and laboratory analysis. Air quality monitoring was conducted at eight locations using Graseby Dust Samplers and Gas Impingers to measure PM₁₀, PM₂.₅, SO₂, NO₂, CO, and HC, following Government Regulation No. 41/1999. Results indicate that PM₁₀ levels (22 µg/Nm³) remained within regulatory limits, while CO (578 µg/Nm³) and NO₂ (35.6 µg/Nm³) fluctuated with construction intensity. Mitigation strategies such as water spraying and project vehicle management effectively reduced dust and gas emissions. Continuous monitoring is essential to minimize air pollution impacts. This study provides empirical data to support sustainable infrastructure development, balancing economic benefits with environmental conservation.